Determination of moisture content in oil palm fruits using a five-port reflectometer - Yee, Lee Kim; Zulkifly, Abbas; Mohamad Ashry, Jusoh; You, Kok Yeow; Cheng, Ee Meng (MDPI Publishing, 2011)
Link to publisher's hompage at http://www.mdpi.com/